Tracking Changes in US Organizations' Workplace Health Promotion Initiatives: A Longitudinal Analysis of Performance Against Quality Benchmarks. Issue 2 (February 2020) - Weaver, GracieLee M.; Bibeau, Daniel L.; Rulison, Kelly; Bray, Jeremy; Dudley, William N.; Unsal, Nilay
Purpose: To examine changes in organizations' workplace health promotion (WHP) initiatives over time associated with repeated self-assessment using the Well Workplace Checklist (WWC). Design: Well Workplace Checklist data include a convenience sample of US organizations that selected to assess their performance against quality WHP benchmarks. Setting: Workplaces. Subjects: In total, 577 US organizations completed the WWC in 2 or more years from 2008 to 2015. Measures: The WWC is a 100-item organizational assessment that measures performance against the original set of quality benchmarks that were established by the Wellness Council of America (WELCOA). Analysis: This study examined changes in overall WWC scores as well as 7 separate benchmark scores. Multilevel modeling was used to examine changes in scores associated with repeated assessments, controlling for the year of assessment and organizational characteristics. Results: There were significant increases in overall WWC scores (β = 2.93, P < .001) associated with the repeated WWC assessments, after controlling for organizational characteristics. All 7 benchmark scores had significant increases associated with reassessment. Compared to other benchmarks, operating plan (β = 6.18, P < .001) and evaluation (β = 4.91, P < .001) scores increased more with each reassessment. Conclusion: Continued reassessment may represent more commitment to and investment in WHP initiatives which could lead to improved quality. Other factors that may positively influence changes in performance against benchmarks include company size, access to outside resources for WHP, and a history with implementing WHP.